Low-cost piezoelectric footswitch system for measuring temporal parameters during walking - Balbinot, Gustavo; Schuch, Clarissa Pedrini; Zaro, Milton Antonio; Vaz, Marco Aurélio (International Journal of Engineering and Technology, 2014)
Human walking is one of the most investigated biomechanical events, and gait analysis depends on accurate measurement of heel strike (HS) and toe off (TO). The purpose of this study was to construct and validate a low-cost footswitch system for the measurement of temporal gait parameters. Ten young healthy subjects participated of the validation and test of the footswitch system with two different footwear, Bland-Altman analysis showed 98% and 95% of validation data within the limits of agreement, for HS and TO respectively (mean difference of 16ms±1ms and 20ms±9ms) and the temporal parameters measured during treadmill walking at a speed of 4.5km.h-1 showed results similar to those found in the literature for normal walking. The outcomes confirm low CoVs for the instrumented athletic and instability shoe, respectively: (1.52±0.61)% and (1.90±0.73)% for contact time, (2.17±0.95)% and (2.57±0.95)% for balance time, (0.84±0.28)% and (1.12±0.53)% for stride time. The low-cost footswitch system described and validated in the present study has an important practical applicability, mostly for emerging and developing countries biomechanics labs. Keywords: Footswitch System, Gait Analysis, Locomotion, Low-Cost, Walk.